Exploratory Use of PPG Signal in Continuous Authentication - Dias, Júlio da Silva; Traore, Issa; Ferreira, Vitor G. R. A.; Ardigo, Julibio David; De Rolt, Carlos Roberto (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2015: Anais do XV Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2015.20091, 2015)
One-time or static authentication is not sufficient in many applications and continuous authentication methods can provide a way to increase security in situations where an application could be compromised or misused after statically authenticating the user. The aim of this work is to evaluate the use of the Photoplethysmographic Signal (PPG) in continuous authentication and identify the requirements of the system that should be used to record and process the signal. Different types of sensors, sampling rates, and analog to digital conversion resolutions were tested in order to identify the configuration that best suits the application requirements. The algorithms used for processing the PPG signal as well as the size of the samples used in the authentication process were also analyzed during the experiments. In order to achieve the set objective, a dataset of PPG signals was developed since it was not possible to find open datasets with long term monitoring samples of individuals.